PERSEPSI PENGUNJUNG TERHADAP DAYA TARIK TAMAN WISATA ALAM HUTAN RIMBO TUJUH DANAU DI DESA WISATA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR RIAU - Devola Martania Fentri; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research purposed to get known about: how the tourist perception of Taman Wisata Alam Hutan Rimbo Tujuh Danau in Buluh Cina tourism village sub district Siak Hulu, district Kampar Riau. This research is a quantitative research with respondents consisting of 82 visitors who came to Hutan Rimbo Tujuh Danau in Buluh Cina tourism village at Kampar Regency of Riau. The determination of respondents by accidental sampling data collection is done by observation, questionnaire and documentation based on research which has been in the existing facilities at Taman Wisata Alam Hutan Rimbo Tujuh Danau is not adequate. This is because there are still facilities that have not been functioned optimally and received less attention from the manager of Taman Wisata Alam Hutan Rimbo Tujuh Danau in Buluh Cina tourism village Siak Hulu District Kampar Riau.Keywords : Visitor Perception, Attraction, Nature Tour.